Chloride channel and chloride conductance regulator domains of CFTR, the cystic fibrosis transmembrane conductance regulator - Schwiebert, Erik M. (The National Academy of Sciences, 1998)
CFTR is a cyclic AMP (cAMP)-activated chloride (Cl(−)) channel and a regulator of outwardly rectifying Cl(−) channels (ORCCs) in airway epithelia. CFTR regulates ORCCs by facilitating the release of ATP out of cells. Once released from cells, ATP stimulates ORCCs by means of a purinergic receptor. To define the domains of CFTR important for Cl(−) channel function and/or ORCC regulator function, mutant CFTRs with N- and C-terminal truncations and selected individual amino acid substitutions were created and studied by transfection into a line of human airway epithelial cells from a cystic fibrosis patient (IB3–1) or by injection of in vitro transcribed complementary RNAs (cRNAs) into Xenopus oocytes. Two-electrode voltage clamp recordings, (36)Cl(−) efflux assays, and whole cell patch-clamp recordings were used to assay for the Cl(−) channel function of CFTR and for its ability to regulate ORCCs. The data showed that the first transmembrane domain (TMD-1) of CFTR, especially predicted α-helices 5 and 6, forms an essential part of the Cl(−) channel pore, whereas the first nucleotide-binding and regulatory domains (NBD1/R domain) are essential for its ability to regulate ORCCs. Finally, the data show that the ability of CFTR to function as a Cl(−) channel and a conductance regulator are not mutually exclusive; one function could be eliminated while the other was preserved.